THE RELATIONSHIP AND DIFFERENCES IN GENDER BETWEEN LANGUAGE LEARNING STRATEGIES AND STUDENTS’ ENGLISH ACHIEVEMENT IN SENIOR SECONDARY SCHOOL - Hamsinah Hamsinah (Elite : English and Literature Journal, 2017)
AbstractThis research was intended to find out: (1) the language learning strategies that are frequently used by the students; (2) whether or not there is any significant relationship between the use of language learning strategies and the English achievement of the students; (3) whether or not there is any significant difference in language learning strategies use due to gender; and (4) whether or not there is any significant difference of students’ English achievement due to gender. This research applied correlational research which deals with two predictors and one criterion variable. The population of this research was the students of grade XI IPA of SMAN 1 Bajeng, Gowa Regency, South Sulawesi Province. The sample was taken by using proportional stratified random sampling technique. Therefore, the sample consisted of 76 students which were divided 38 females and 38 males. The data of this research were collected through SILL questionnaire and the test. The data were analyzed by using descriptive and inferential statistics through SPSS program version 20. Depending on the statistical results, the findings revealed that first of all, social strategies were the frequently language learning strategies used by the students and followed by metacognitve strategies. Second, there was no any significant relationship between language learning strategies (LLSs) and the English achievement of the students where the correlation coefficient was r =.182 at p > 0.05. Third, there was no any significant difference in language learning strategies use due to gender where the computed ttest for the six types and the overall of language learning strategies (LLSs) were ttest = .539, -1.077, .850, -1.078, -.693, -1.109, and -.725 at p > 0.05. Fourth, there was a significant difference of students’ English achievement due to gender where ttest = 3.24 at p < 0.05. It indicated that female students more successful than male students in learning English.AbstrakPenelitian ini bertujuan untuk mengetahui: (1) strategi pembelajaran bahasa yang sering digunakan oleh siswa; (2) apakah ada hubungan yang signifikan antara penggunaan strategi pembelajaran bahasa dan hasil belajar bahasa Inggris siswa; (3) apakah ada perbedaan yang signifikan dalam strategi pembelajaran bahasa yang digunakan yang disebabkan oleh jenis kelamin; dan (4) apakah ada perbedaan yang signifikan antara hasil belajar bahasa Inggris siswa yang disebabkan oleh jenis kelamin. Penelitian ini menggunakan penelitian korelasional yang membahas dua variable prediktor dan satu variabel kriteria. Populasi penelitian ini adalah siswa kelas XI IPA SMAN 1 Bajeng, Kabupaten Gowa, Provinsi Sulawesi Selatan. Sampel diambil dengan teknik proportional stratified random sampling. Oleh karena itu, sampel terdiri dari 76 siswa yang dibagi 38 perempuan dan 38 laki-laki. Data penelitian ini dikumpulkan melalui kuesioner SILL dan tes. Data dianalisis dengan menggunakan statistik deskriptif dan inferensial melalui program SPSS versi 20. Berdasarkan pada hasil statistik, temuan tersebut mengungkapkan bahwa pertama, strategi sosial adalah strategi pembelajaran bahasa yang sering digunakan oleh siswa dan diikuti oleh strategi metakognitif. Kedua, tidak ada hubungan yang signifikan antara strategi pembelajaran bahasa (LLSs) dan prestasi bahasa Inggris siswa dimana koefisien korelasinya adalah r = 0,182 pada p> 0,05. Ketiga, tidak ada perbedaan yang signifikan dalam strategi pembelajaran bahasa yang digunakan karena jenis kelamin di mana metode yang dihitung untuk enam jenis dan keseluruhan strategi pembelajaran bahasa (LLSs) adalah ttest = 0,539, -1,077, 0,850, -1,078, - 0,693, -1,109, dan -0,725 pada p> 0,05. Keempat, terdapat perbedaan yang signifikan dari hasil belajar bahasa Inggris siswa yang disebabkan oleh jenis kelamin dimana ttest = 3,24 pada p <0,05. Ini menunjukkan bahwa siswa perempuan lebih berhasil daripada siswa laki-laki dalam belajar bahasa Inggris.